2016
DOI: 10.1021/acs.nanolett.6b01411
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Delivery of Nanolabels Prevents Their Asymmetric Inheritance and Enables Extended Quantitative in Vivo Cell Imaging

Abstract: Long-term in vivo imaging of cells is crucial for the understanding of cellular fate in biological processes in cancer research, immunology or in cell-based therapies such as beta cell transplantation in type I diabetes or stem cell therapy. Traditionally, cell labelling with the desired contrast agent occurs ex vivo via spontaneous endocytosis, which is a variable and slow process that requires optimization for each particular label-cell type combination. Following endocytic uptake, the contrast agents mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 57 publications
3
66
0
Order By: Relevance
“…A wide range of therapeutically relevant cargoes are within this size range, including transcription factors, antibodies, and genome-editing nucleases [15]. Our results are in agreement with a previous study from our group on HeLa cells [55], and suggested that the VNB-induced pores can have a size of up to 30 nm, as inferred by the observed influx of 500 kDa dextrans. For the efficient delivery of cargoes of this size, the generated membrane pores should be big enough and remain open sufficiently long for these larger and slowly diffusing molecules to be able to reach the cell cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…A wide range of therapeutically relevant cargoes are within this size range, including transcription factors, antibodies, and genome-editing nucleases [15]. Our results are in agreement with a previous study from our group on HeLa cells [55], and suggested that the VNB-induced pores can have a size of up to 30 nm, as inferred by the observed influx of 500 kDa dextrans. For the efficient delivery of cargoes of this size, the generated membrane pores should be big enough and remain open sufficiently long for these larger and slowly diffusing molecules to be able to reach the cell cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…The micelles in early endosomes then quickly transformed into a dissociated state from 5 to 25 min, which was consistent with the classical endocytosis process. [ 34 ] At 4 °C, the strong blue fluorescence signal from TPE in early endosomes was maintained over 25 min, suggesting that the dispersing process of PTI micelles in the early endosome was delayed due to the decreased molecule velocity in the low temperature. [ 35 ] The PTI micelles were gradually delivered to lysosomes from 25 to 60 min (Pearson's coefficient of ICGD/lysosome: 0.584, Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…To maximize reporter labeling, fluorescent polymeric NPs and quantum dots (QDs) have been used to label and monitor SCs [15], as well as monitor their accumulation in wound healing using a chemoattractants [100]. An interesting method of cell labeling is the direct introduction of reporter into the cytoplasm using sonoporation with US and MB, or photoporation with light and gold nanoparticles [101]. Using photoporation, Xiong et al showed a several-fold increase in labeling efficiency, symmetric signal distributed to daughter cells and the reporter remained visible for 2 months rather than 2 weeks [101].…”
Section: Optical Imagingmentioning
confidence: 99%
“…An interesting method of cell labeling is the direct introduction of reporter into the cytoplasm using sonoporation with US and MB, or photoporation with light and gold nanoparticles [101]. Using photoporation, Xiong et al showed a several-fold increase in labeling efficiency, symmetric signal distributed to daughter cells and the reporter remained visible for 2 months rather than 2 weeks [101].…”
Section: Optical Imagingmentioning
confidence: 99%